2017
DOI: 10.4049/jimmunol.1700426
|View full text |Cite
|
Sign up to set email alerts
|

Factor H–IgG Chimeric Proteins as a Therapeutic Approach against the Gram-Positive Bacterial PathogenStreptococcus pyogenes

Abstract: Bacteria can cause life-threatening infections, such as pneumonia, meningitis or sepsis. Antibiotic therapy is a mainstay of treatment, although antimicrobial resistance has drastically increased over the years. Unfortunately, safe and effective vaccines against most pathogens have not yet been approved, thus developing alternative treatments is important. We analyzed the efficiency of FH6-7/Fc, a novel antibacterial immunotherapeutic protein against the gram-positive bacterium Streptococcus pyogenes. This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 65 publications
(75 reference statements)
0
28
0
Order By: Relevance
“…Because complement-inhibitory activity of C4BP requires the third CCP domain (23), these fusion proteins should not inhibit complement, while they should preserve the ability to deposit on bacteria. Previous work by our groups have shown that a chimeric protein that comprises the microbial binding domains of another complement inhibitor, factor H (FH), fused to Fc is efficacious in vitro and in vivo against Streptococcus pyogenes (24), N. gonorrhoeae (7), N. meningitidis (25), and Haemophilus influenzae (26) and provided the rationale for targeting N. gonorrhoeae-C4BP interactions. The isolates are grouped according to their expressed subclass of PorB and anatomical site of isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Because complement-inhibitory activity of C4BP requires the third CCP domain (23), these fusion proteins should not inhibit complement, while they should preserve the ability to deposit on bacteria. Previous work by our groups have shown that a chimeric protein that comprises the microbial binding domains of another complement inhibitor, factor H (FH), fused to Fc is efficacious in vitro and in vivo against Streptococcus pyogenes (24), N. gonorrhoeae (7), N. meningitidis (25), and Haemophilus influenzae (26) and provided the rationale for targeting N. gonorrhoeae-C4BP interactions. The isolates are grouped according to their expressed subclass of PorB and anatomical site of isolation.…”
Section: Introductionmentioning
confidence: 99%
“…FreeStyle Chinese hamster ovary (CHO) S suspension cells (Life Technologies), grown in FreeStyle CHO expression medium supplemented with 8 mM L-glutamine were used for the expression of FH6-7/IgG fusion protein as described ( 22 ). Cell cultures were grown in 250 ml Erlenmeyer flasks at 37°C with 8% CO 2 with shaking (130 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…The net result is displacement of complement inhibitors from the bacterial surface with simultaneous complement activation via Fc-C1q interaction, which increases pathogen elimination. This approach has shown promise in enhancing killing of Non-typeable Haemophilus influenzae (NTHi) ( 20 ), Neisseria meningitidis ( 18 ), Neisseria gonorrhoeae ( 19 , 21 ), and Streptococcus pyogenes ( 22 ). In this study we tested the bactericidal activity of both fusion proteins against M. catarrhalis .…”
Section: Introductionmentioning
confidence: 99%
“…Using S. pyogenes as an example, we investigated if FH-IgG would have an antibacterial effect on Gram-positive bacteria as well. Indeed, we observed binding of FH-IgG to the bacteria and a displacement of serum FH from the bacterial surface, leading to increased MAC deposition [22]. Increased killing, however, was not observed in serum sensitivity assays, but only when co-incubated in whole blood.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Similar to M proteins, protein H also presents a coiled-coil dimer structure with a heptad repeat pattern [21]. It can bind to a variety of human serum proteins, such as albumin, the complement inhibitors FH and C4BP, and IgG, via their Fc portion [12, 14, 15, 22]. Interestingly, certain ligands such as IgG or albumin as well as temperature can influence the structure of protein H and the M proteins [21, 23].…”
Section: Surface-bound Virulence Factorsmentioning
confidence: 99%